The Kiai of the Makrifatul Ilmi Islamic Boarding School in South Bengkulu's Role in Empowering Community Character - Intan Utami (Lembaga Riset dan Inovasi Almatani, 2023)
Boarding school education is an efficient merger of Islamic boarding school and madrasah education systems for education, skills intelligence, character development, and teaching moral principles in pupils, resulting in individuals with complete and distinct personalities. The goal of this study is to find out what function the Kiai of the Makrifatul Ilmi Islamic Boarding School in South Bengkulu plays in boosting community character. This sort of research employs qualitative research, also known as naturalistic research because the research is conducted in natural settings. According to the findings of the study, the role of chaplains at the Makrifatul Ilmi Islamic Boarding School in South Bengkulu in Community Empowerment is a program designed to shape the Islamic character or attitudes of the community so that they become better and more accustomed to it in everyday life. In terms of societal implementation, the paradigm used at the Makrifatul Ilmi Islamic Boarding School is as follows: First, knowledge, namely the ability for people to understand numerous areas, particularly religion. Being religious entails making every effort to condition people's conduct to diligently implement and carry out religion in daily life, particularly in terms of worship and good acts.